2015
DOI: 10.1111/jnc.13084
|View full text |Cite
|
Sign up to set email alerts
|

Brain area‐specific diurnal and photic regulation of val‐opsinA and val‐opsinB genes in the zebrafish

Abstract: Zebrafish possess two isoforms of vertebrate ancient long (VAL)-opsin, val-opsinA (valopa) and val-opsinB (valopb), which probably mediate non-visual responses to light. To understand the diurnal and light-sensitive regulation of the valop genes in different cell groups, the current study used real-time quantitative PCR to examine the diurnal changes of valopa and b mRNA levels in different brain areas of adult male zebrafish. Furthermore, effects of the extended exposure to light or dark condition, luminous l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…Non‐mammalian vertebrates possess a wide range of intrinsically photoreceptive sites expressing members of the non‐visual opsin family (see Hankins, Davies, & Foster, ). ISH studies in the brain of zebrafish and other teleosts have revealed different neuronal populations that express opsins (Philp et al, ; Matos‐Cruz et al, ; Fischer et al, ; Nakane et al, ; Eilertsen et al, ; Hang, Kitahashi, & Parhar, ; Sato et al, ). Some of the Opn5 (neuropsin)‐expressing forebrain populations of medaka and zebrafish (Sato et al, ) are located in regions similar to those containing the post‐optic/hypothalamic opsin and/or transducin‐expressing CSF‐c neuronal populations of lampreys (García‐Fernández & Foster, ; García‐Fernández et al, ; present results).…”
Section: Discussionmentioning
confidence: 99%
“…Non‐mammalian vertebrates possess a wide range of intrinsically photoreceptive sites expressing members of the non‐visual opsin family (see Hankins, Davies, & Foster, ). ISH studies in the brain of zebrafish and other teleosts have revealed different neuronal populations that express opsins (Philp et al, ; Matos‐Cruz et al, ; Fischer et al, ; Nakane et al, ; Eilertsen et al, ; Hang, Kitahashi, & Parhar, ; Sato et al, ). Some of the Opn5 (neuropsin)‐expressing forebrain populations of medaka and zebrafish (Sato et al, ) are located in regions similar to those containing the post‐optic/hypothalamic opsin and/or transducin‐expressing CSF‐c neuronal populations of lampreys (García‐Fernández & Foster, ; García‐Fernández et al, ; present results).…”
Section: Discussionmentioning
confidence: 99%
“…Most animals also possess multiple opsins that underlie non-visual functions such as circadian photoentrainment, suggesting their possible diverse and complicated involvement in varied types of non-visual photoreception [ 4 7 ]. However, the significance of the diversification of non-visual opsins remains uncertain, although comparative studies of duplicated non-visual opsins such as melanopsin and vertebrate ancient-long (VAL)-opsin have revealed differences in their expression patterns [ 8 12 ]. The pineal and related organs of non-mammalian vertebrates are a good model for examining this issue because they are photosensitive organs with diverse functions.…”
Section: Introductionmentioning
confidence: 99%
“…In the zebrafish, the VAL-opsin isoforms are expressed in both the eyes and the brain [10, 11, 15], and the VAL-opsin photoreceptors in the eyes and the brain are thought to play distinct roles in zebrafish physiology [16]. Furthermore, VAL-opsinA and VAL-opsinB photoreceptors are expected to have distinct functions in the eyes [11].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, F0 valopa and valopb mutants exhibited a similar parental-effect phenotype in their eggs and resultant embryos. Our previous work determined the co-expression of valopa and valopb in the thalamic valop cell group within the brain, which may play a GABA-dependent modulatory role in light-dependent physiology [15, 16]. There is evidence of seasonal variation in the levels of GABA-synthesizing enzymes in the brain and GABA control on pituitary gonadotropin release in fish species [5357].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation